Revenge, Agency, and Identity from European Drama to Asian Film : Agents of Vengeance - Dodson-Robinson, Eric, (Metaforms, 2019)
Eric Dodson-Robinson's Revenge, Agency, and Identity from European Drama to Asian Film challenges critical readings of drama, film, and literature that downplay agency. From Attic tragedy, through Seneca and Shakespeare, and into Japanese and Korean film, the book pursues the agent of vengeance in her fury to reconstruct an identity shattered by trauma. Tragic revenge is an imaginary theater only partly encompassed by disciplines, institutions, and discourses. In this theater, violence becomes contagious and potentially transformative as performance gives birth to the agent of vengeance: a complex, emergent agent who is more than the sum of the actors, auteur, tradition, and audience, all of whom infiltrate, and strive to control, her will. The agent of vengeance, determined to outdo past exemplars, exacts traumatic excess, not equivalence.